Numerical software verification : 9th International Workshop, NSV 2016, Toronto, ON, Canada, July 17-18, 2016, Revised selected papers /: 9th International Workshop, NSV 2016, Toronto, ON, Canada, July 17-18, 2016, Revised selected papers. (2017) - Unknown
No abstract available